Feira das Manas: economia criativa, empoderamento e sustentabilidade em Palmas/TO - Castilho, Juliana Abrão da Silva (Universidade Federal do Tocantins, 2024)
In Palmas/TO, a group of artisans structured themselves under the auspices of female empowerment and creative economy and founded a traveling fair. The "Feira das Manas", organized through social networking movements online, presents itself as a sustainable model for generating employment and income for women through creative economy. The perspective developed in the analysis is supported by the theoretical framework of Social Psychology, specifically the Theory of Social Representations, as analyzed in this document. The theoretical framework seeks to establish the city of Palmas as a stage for the group's development, as well as to address the main aspects of the units and categories that support the analysis. The aim is to provide theoretical support for discussions based on data collection. This manuscript also retraces the methodological path followed for the development of the research and the integration of different data collection and analysis instruments. Through netnography and interviews, the formation of the group, its journey during the period of social distancing prompted by the COVID-19 pandemic, and the strategies for the fair's return to the urban environment are recounted. The aim is to relate the fair locations and the imaginary structures present in the group, as well as the construction of an identity performance based on sustainability, female empowerment, and creative economy, as significant social representations for the group.